INTEGRATING ISLAMIC VALUES INTO ENGLISH LEARNING: PERSPECTIVES AND PRACTICES AT MA DARUL ILMI BANJARBARU - Maulydia R, Shania; Maulidiyah, Noor (ENGLISH, 2026)
The importance of considering English language teaching (ELT) strategies in Islamic schools (Madrasah) is crucial for integrating Islamic values ​​and religious identity amidst the dynamics of global education. However, there is often a gap between the ideal theory of value integration and the practice of daily implementation in the classroom, where value integration is often considered an additional burden, rather than an integral part of the language acquisition process. This study aims to describe the practice of integrating Islamic values ​​into English teaching in a Madrasah through a qualitative approach with a case study design, involving the principal, vice-principal, two English teachers, and three students. Data were collected through observation, documentation, and interviews to ensure validity. The results show that Islamic values ​​are systematically integrated in the planning, implementation, and evaluation stages of learning, including through the selection of materials, text contexts, and classroom activities containing moral and religious values. However, this study also found several challenges, such as limited integrated teaching materials and teacher preparation time. In conclusion, the integration of Islamic values ​​in ELT not only strengthens English language learning but also strengthens students' Islamic identity, providing a foundation for the development of contextual and character-oriented English language learning strategies in Madrasah.